A Quasi-Experimental Study Examining the Impact and Challenges of Implementing a Fitness-Based Health Risk Assessment and a Physical Activity Counseling Intervention in the Workplace Setting - Naomi C. Hamm; D. Scott Kehler; Jacqueline L. Hay; Andrew N. Stammers; Shaelyn M. Strachan; Danielle R. Bouchard; Todd A. Duhamel (SAGE Publishing, 2019)
Objectives: Few adults participate in enough physical activity for health benefits. The workplace provides a unique environment to deliver heath interventions and can be beneficial to the employee and the employer. The purpose of the study was to explore the use of a physical activity counseling (PAC) program and a fitness-based health risk assessment (fHRA) in the hospital workplace. Methods: A workplace-based intervention was developed utilizing a PAC program and an fHRA to improve physical activity levels of employees. Hospital employees were enrolled in a 4-month PAC program and given the option to also enroll in an fHRA program (PAC + fHRA). Physical activity was assessed by accelerometry and measured at baseline, 2 months, and 4 months. Changes in musculoskeletal fitness for those in the fHRA program were assessed at baseline and 2 months. Results: For both groups (PAC n = 22; PAC + fHRA n = 16), total and moderate to vigorous physical activity in bouts of 10 minutes or more increased significantly by 18.8 ( P = .004) and 10.2 ( P = .048) minutes per week at each data collection point, respectively. Only participants with gym memberships demonstrated increases in light physical activity over time. Those in the fHRA group significantly increased their overall musculoskeletal fitness levels from baseline levels (18.2 vs 21.7, P < .001). There was no difference in the change in physical activity levels between the groups. Conclusions: A PAC program in the workplace may increase physical activity levels within 4 months. The addition of an fHRA does not appear to further increase physical activity levels; however, it may improve overall employee musculoskeletal fitness levels.